Analysis of Junior High School Students’ Mathematical Literacy Processes (Formulating, Employing, and Interpreting) in PISA Space and Shape - Abirrotun Nabilah; Mauliddiyah Istiqomah; Hendri Handoko (Universitas Islam Tribakti Lirboyo Kediri, 2026)
This study aims to describe students’ mathematical literacy processes when solving PISA problems in the Space and Shape content domain, based on the three PISA literacy processes: Formulating, Employing, and Interpreting. This research uses a descriptive qualitative approach with three ninth-grade students as subjects, selected through purposive sampling: S1 (moderate ability), S2 (low ability), and S3 (high ability). Data were collected through a mathematical literacy test consisting of three PISA Space and Shape problems (Problem 1, Problem 2, and Problem 3) and semi-structured interviews. Data analysis was conducted through data reduction, coding based on literacy process indicators, data display, and conclusion. The results show that S1, in Problem 1, was able to fulfil all mathematical literacy processes (Formulating, Employing, and Interpreting). S2, in Problem 2, was only partially able to achieve the Formulating stage and experienced difficulties with the Employing and Interpreting stages. Meanwhile, S3, in Problem 3, also only partially achieved the Formulating stage and failed to achieve the Employing and Interpreting stages due to an inaccurate mathematical model and inappropriate procedures. These findings indicate that the level of mathematical literacy achievement is not always aligned with students’ ability categories but is influenced by the characteristics of the problem and the accuracy of mathematical modelling. Therefore, learning should emphasise modelling activities, meaningful application of procedures, and interpretation of results in real-world contexts.